Motivation, anxiety, depression and stress in university athletes in times of health restrictions caused by the covid 19 pandemic (RIAF. International Journal of Physical Activity, 2023)
During the pandemic, a series of adaptive processes took place for the global population. Specifically, this research aims to investigate the psychological variables of motivation, anxiety, stress, and depression in university athletes returning to in-person activities in July 2022, both academic and athletic, while still facing health restrictions due to COVID-19. Since 2020, when the pandemic began in Chile, no in-person activities have been held in any university centers. In this context, there is a need to understand the state of the aforementioned variables in university athletes, as the new adaptive process of returning to in-person activities, combined with the inability to pursue national competitive goals, presents a problem to be addressed.The objective of the study is to assess the variables of motivation, anxiety, stress, and depression in active university athletes during their return to in-person academic and athletic activities, despite ongoing restrictions due to the COVID-19 pandemic. The methodology used is quantitative, with an exploratory cross-sectional design. The results presented in this study show a relationship between motivation and depression (
Keywords: Motivation; Anxiety; Depression; Stress; University